Edukasi Kesehatan Reproduksi pada Remaja untuk Menghadapi 1000 Hari Pertama Kehidupan - Desmawati Desmawati (Jurnal Abdimas Kesehatan (JAK), 2020)
Reproductive health education in female adolescent to face the first 1000 days of human life involving: knowledge about  270  days of pregnancy such as knowledge of pregnancy, assestment of pregnancy in health services, breast care, body and clothes hygiene, dental hygiene, imunization  before and during of pregnancy, nutrition for female adolescent and pregnant women, taking early breastfeeding initiation,  and continue to give exclusive breastfeeding. Knowledge for 730 days after delivery involving knowledge about health card for toddlers, immunization for baby, growth and development of child 0 - 23 months, providing nutrition for 0-6 months and 7-24 months.The aim of this health services to improve knowledge of female adolescent about  the first 1000 days of human life. This study methode using health education to increase knowledge of adolescent. The results revealed that health education and demonstration can improve the knowledge of female adolescent about the first 1000 days of human life.